The OCCUPATIONAL SAFETY AND HEALTH RISK ANALYSIS IN THE FRAMEWORK OF IMPROVING PRODUCTION SAFETY IN THE PRODUCTION AREA (Case Study at Gama Steel Solo): ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA DALAM RANGKA PERBAIKAN PRODUCTION SAFETY DI AREA PRODUKSI (Studi Kasus di Gama Steel Solo) - Abed Rozaq; Erna Indriastiningsih; Yunita Primasanti (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2025)
Occupational safety and health (OHS) is a crucial aspect that must be considered in every industry, including production environments involving heavy machinery and complex processes, which are often the site of workplace accidents. OHS analysis is crucial for ensuring worker safety and security, as well as identifying areas for improvement. This study aims to analyze the implementation of occupational safety and health (OHS) in the production area of PT Gama Steel Solo using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. The results indicate that across seven main types of work in the production area, 34 potential hazards were identified, with 35 risks classified by risk level: 3 low risks, 9 moderate risks, 14 high risks, and 9 extreme risks. Based on the HIRARC analysis, several recommended risk control measures include engineering controls, administrative controls, and the use of personal protective equipment (PPE) in accordance with established standards. This study concludes that the HIRARC approach is effective in supporting companies to systematically identify hazards, conduct risk assessments, and provide a basis for decision-making/control recommendations to improve production safety. Keywords: Work Safety, HIRARC, Personal Protective Equipment, Danger, Risk